Validity and Reliability Test of Self-Efficacy Scale: A Structure Equation Modelling Approach: Validity and Reliability Test of Self-Efficacy Scale: A Structure Equation Modelling Approach - Ariska, Desi; Diponegoro, Ahmad; Tentama, Fatwa (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2021)
Research on self-efficacy is hotly discussed, especially in this time of pandemic. As for knowing the high or low self-efficacy, a valid and reliable measuring instrument is needed. The purpose of this study was to develop a teacher self-efficacy scale using SEM modeling based on Bandura's theory. The aspects of self-efficacy that are used as a reference for making measuring instruments consist of level, strength, and generality. The study was conducted on 100 Vocational High School teachers. The measuring instrument is arranged using the Likert model. The validity and reliability test used the confirmatory factor analysis (CFA) approach with the help of PLS ​​3.29 software. The results showed that the self-efficacy measurement tool was declared valid and reliable because all items from the dimensions were able to reflect the 110 constructs that were formed. This measuring instrument is also declared valid and reliable where there are 12 items that have fallen out of the 30 items submitted.